Late Medieval Bone and Antler Working at the Residence of the Archbishop of Esztergom (Northern Hungary) - Gál, Erika (Archaeologia Lituana, 2020)
A relatively small worked bone and antler assemblage including 28 finished objects and 104 remains representing blanks and waste material was identified during the zooarchaeological analysis of the bone material found at the recently excavated site of Esztergom-Várhegy-Kőbánya (Esztergom-Castle Hill-Quarry). According to archaeological investigations, the complete animal bone assemblage deposited in several successive layers on the Castle Hill of Esztergom represents the kitchen refuse of the bishopric residence. Despite the religious context of the settlement, rosary beads or other artefacts usually produced in greater numbers are missing in our material. Common objects such as pins, handles and toys as well as the fine worked decorative items were poorly represented. Contrary, the details for crossbow and the antler debris dominated the assemblage linked to manufacturing. All these would suggest the presence of a workshop in the archbishop’s palace specialised for the quick production and reparation of details for crossbow. Although the small quantity of both the finished objects and production waste point to a small – maybe only seasonally operating – workshop, the involvement of a skilled bone-worker and possibly a lathe is suggested.
Keywords: bone and antler manufacture; workshop; lathe; bishopric residence; Late Medieval; Esztergom-Várhegy-Kőbánya; Hungary